The Methodology in Empirical Sales Ethics Research: 1980–2010 - McClaren, Nicholas (Journal of business ethics, 2015)
The study examines the research methodology of more than 200 empirical investigations of ethics in personal selling and sales management between 1980 and 2010. The review discusses the sources and authorship of the sales ethics research. To better understand the drivers of empirical sales ethics research, the foundations used in business, marketing, and sales ethics are compared. The use of hypotheses, operationalization, measurement, population and sampling decisions, research design, and statistical analysis techniques were examined as part of theory development and testing. The review establishes a benchmark, assesses the status and direction of the sales ethics research methodology, and helps inform researchers who need to deal with increasing amounts of empirical research. The investigation identified changing sources of publication with the Journal of Business Ethics and the Journal of Personal Selling & Sales Management maintaining their position as the main conduit of high quality empirical sales ethics research. The results suggest that despite the use of theoretical models for empirical testing, a greater variety of moral frameworks and wider use of marketing exchange theory is needed. The review highlights many sound aspects about the empirical sales ethics research statistical methodology but also raises concerns about several areas. Ways in which these concerns might be addressed and recommendations for researchers are provided.